Application of clustering in statistical analysis of music data - Kavaliauskas, Mindaugas (Lietuvos matematikos rinkinys, 2012)
In this article author analyses musical works of Lithuanian compositors using statistical methods. Markov chains are used to describe compositions. Stationary distributions are used as feature vectors for clustering. A few interpretations of clusters are presented. Possibility to use feature vectors to identify the unknown author of composition is tested.